INDIVIDUAL EDUCATIONAL PATHS AS FACTOR OF ENHANCING OF FUTURE TEACHERS TRAINING QUALITY - DOROZHKIN, E. M.; MOSKALENKO, M. R.; LARIONOVA, M. B.; LYZHIN, A. I; KOROTAEV, I. S (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The relevance of the issue under study is conditioned by the importance of enhancing the pedagogical education quality and by the following necessity of implementation of an individual approach and individual educational paths of learning. The article is aimed at studying issues of implementing individual educational paths in the framework of the teaching of pedagogical specialty students for making the quality of their training higher. Ten students of the RSVPU took part in the study. As a result of the analysis, the most effective methods and forms of using individual learning paths in teacher training have been identified.RESUMEN La relevancia del tema en estudio está condicionada por la importancia de mejorar la calidad de la educación pedagógica y por la siguiente necesidad de implementar un enfoque individual y caminos educativos individuales de aprendizaje. El artículo tiene como objetivo estudiar cuestiones de implementación de caminos educativos individuales en el marco de la enseñanza de estudiantes de especialidad pedagógica para mejorar la calidad de su formación. Diez estudiantes de la RSVPU participaron en el estudio. Como resultado del análisis, se han identificado los métodos y formas más efectivos de utilizar las rutas de aprendizaje individuales en la formación del profesorado.